EFEKTIFITAS KONSELING KELOMPOK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMK YANG MENGALAMI KETIDAKSESUAIAN PILIHAN JURUSAN - Umdatul Khoirot (Institut Agama Islam Negeri Ponorogo, 2021)
The purpose of this study was to test the effectiveness of group counseling to increase the motivation of vocational students who experienced a mismatch in the choice of majors. The research subjects were 8 students of class X who experienced a discrepancy in their choice of majors. The research method is a quasi-experimental method with the One-group pretest-posttest design technique. Analysis of the data used is the paired sample t-test to see differences in the learning motivation of SMK students who experience discrepancies in the choice of majors before and after being given treatment. The results showed that there was an increase in students' motivation scores after being given treatment, which means that group counseling was effective in increasing the learning motivation of SMK students who experienced a mismatch in the choice of majors.Keywords: learning motivation, group counseling, incompatibility of choice with majors